The influence of contextual factors on implementation fidelity in a whole school approach to prevention of violence against women. (19th September 2018) - Joyce, Andrew; Ollis, Debbie; Kearney, Sarah; Leung, Loksee; Foenander, Emily
Abstract: Issue addressed: Implementation fidelity relates to the degree of adherence to implementation protocols and content and helps to guide replication of evidence‐based programs. In settings‐based research, notions of fidelity have been applied more often to delivery of education content rather than whole of setting change. The aims of this paper were firstly, to analyse how contextual factors influenced implementation of a whole school program on respectful relationships education, and secondly given the findings, discuss whether a more flexible approach to implementation fidelity may have yielded increased school engagement. Methods: The project was conducted in 19 secondary schools in Victoria in 2015. This paper reports on focus groups and interviews which were conducted with 81 school staff and 28 staff from the lead agency, community agency partners, and departmental staff to understand the contextual factors influencing implementation. Results: The program followed a traditional implementation fidelity approach of considering core elements and some minor scope for adaption which engaged some regions and schools but not others. Conclusion: An alternative notion of implementation fidelity, "fidelity to function, " may have permitted increased flexibility to tailor the intervention components to suit different school and community contexts and potentially, increasing both the reach and impact of the program. So what?: Understanding how to apply notions of fidelity to guide whole of setting change are important considerations if programs are to be replicated to have wider reach and greater impact and effectiveness.